(untitled) (Shiksha Shastra Saurabh, 2025)
This paper gives details on how Bandura’s Social Learning Theory (SLT) describes the persistence of sexual harassment across institutions and generations. It asserts that individuals come to learn, observe, copy and normalize harassment, particularly when such behavior remains unchecked. Utilizing an integrative theoretical review based on systematic literature searches and thematic analysis, the study illustrates how factors like institutional complicity, peer culture, family, and cultural norms facilitate this deviant behavior. Key SLT concepts such as observational learning, vicarious reinforcement, and moral disengagement highlight how harassment becomes an ingrained behavioral script, often perpetuated when perpetrators are not punished or are even rewarded. The concept of reciprocal determinism further clarifies the continuous interplay between personal, behavioral, and environmental factors in sustaining these patterns. The research indicates that learned behavior can be unlearned through positive role models, accountability, and structural interventions. This understanding offers a vehicle for developing more effective education, prevention, and policy interventions to disrupt the social learning chain supporting sexual harassment. While SLT provides a robust framework, the paper acknowledges its limitations in adequately addressing institutionalized power relations and intersectionality.